The challenges of Iranian health system preparedness before earthquakes based on the World Health Organization framework - Mohammad Heidari; Samaneh Heidari; Hamid Jafari (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The state of health-care disaster preparedness in Iran prior to the possible earthquakes is not well documented. This study identified the challenges of the Iranian health system before possible earthquakes in Tehran based on the World Health Organization (WHO) framework. MATERIALS AND METHODS: In this qualitative study, in-depth and semi-structured interviews were conducted for 17 health experts and authorities, who were selected based on purposive sampling method. The questions were designed based on the proposed framework of the WHO in six areas including policies and planning, communication, collaboration and coordination, training, volunteers and the public, and surge capability. The data were analyzed by using framework analysis. RESULTS: The main themes included weak communication infrastructures, inappropriate assessment of specialized training courses and lack of a clear scenario, integrated urban commanding, extra-sectorial coordination, and data banks for public volunteers. CONCLUSION: Iran health-care disaster preparedness was tested by many earthquakes. This research showed that disaster preparedness in Iran faces several challenges.